The Effect of Reciprocal Teaching Model on Students’ Self-Regulated Mathematics Learning in SMPN 2 Patikraja Banyumas Regency - Ulpah, Maria; Zaenurrohman; Sahly, Muh. Naffi (Proceeding International Conference on Science and Engineering, 2020)
In mathematics learning, not only cognitive abilities, but affective abilities also need to be improved, especially the ability to learn independently or self-regulated learning. Self-regulated learning is very important because the attitude of independence aims to be able to direct students towards positive behavior that can support success in the learning process. Self-regulated learning makes students trained and manages every action, so students have discipline in the learning process. Students who have good self-regulated learning can complete the task and are able to overcome a learning problem. The learning model that is thought to improve self-regulated learning is reciprocal teaching. This model requires students to study independently with strategies to summarize, make questions, explain, and predict answers. This research uses quantitative approach with a quasi-experiment, conducted in 8th grade of SMPN 2 Patikraja, Banyumas Regency. The instrument used to measure self-regulated learning is a questionnaire consisting of 24 valid questions. The results of this study indicate that there is an effect of the reciprocal teaching model on students' self-regulated mathematics learning. This can be seen from the average score of n-gain 0.353 in the medium category.